The evolution of the effectiveness of the forces to ensure and restore public order and security in the context of sports events - TALMACI Valentin (Editura Univeristatii "Stefan cel Mare" din Suceava, 2024)
The effectiveness of law enforcement in ensuring and restoring public order and security has evolved significantly over time, influenced by multiple factors, including technological innovations, legislative changes, professional training and international cooperation. This aspect is particularly important in the context of sporting events, which gather a large number of participants and potential risks. The purpose of this article is to increase the efficiency and remediation of the operative actions of law enforcement during public and sports events. The results of the mathematical modeling showed that the time of the actions of the forces to ensure public order for exceptional situations is 2.73 times higher than the standard ones according to the existing techniques and 2.68 times - in the case of applying the proposed techniques. The total time of the actions of the forces to ensure public order is 38% lower in the case of the application of the proposed techniques compared to the existing onesTimpul acțiunilor forțelor la restabilirea ordinii publice pentru situații excepționale este mai mare decât celor standard de 1,63 ori conform tehnicilor existente și de 1,75 ori - în cazul aplicării tehnicilor propuse. The total time of the actions of the forces to restore public order is lower by 29% in the exceptional case and the application of the proposed techniques compared to the existing ones. The total time of force actions to restore public order is 33% less in the standard case and the application of the proposed techniques compared to the existing ones.